The current state of Carceral health data: an analysis of "Listening Sessions" with stakeholders - Zaire Cullins; Michael Forrest Behne; Lauren Brinkley-Rubinstein (BMC, 2023)
Abstract Background Understanding the health conditions of those under carceral control is often made difficult due to lack of access to data. Yet, as has been made clear during the COVID-19 pandemic, is that data is essential to understand the scope of disease and how best to allocate resources. To better understand the needs of criminal legal oriented research and non-profit organizations, we interviewed stakeholders to better understand how they use existing data, what data they lack, and what data they would like to have to optimally assess the health of people who are incarcerated. Results Stakeholders reported a lack of trust and data availability as key issues. Many perceived the few institutions that do collect and disseminate data as obfuscating data or having a bias in collection and reporting. Additionally, concerns such as balancing the interest of systems-impacted people with advocacy were described as concerning for participants. Conclusions To tackle these issues of transparency and availability, the authors believe that an independent oversight body could be instrumental to ensuring accurate and timely data collection and reporting. As many participants turned to creating their own data, coalition building could be influential as a large network of resources may support capturing the varied experiences of people who are incarcerated.